REMOTE SENSING OF AMAZONIAN FORESTS: MONITORING STRUCTURE, PHENOLOGY AND RESPONSES TO ENVIRONMENTAL CHANGES - dos Santos, João Roberto; Galvão, Lenio Soares; Aragão, Luiz Eduardo Oliveira e Cruz de (Revista Brasileira de Cartografia, 2014)
Remote sensing is a key tool for studying the tropical Amazonian forests, which have a substantial role on the global climate system and on the carbon and water cycles. In this article, we overview recent advances in remote sensing for estimating tropical forest structure and biomass, for analyzing phenological patterns across tropical landscapes, and forquantifying the impacts of natural and human-induced environmental changes on this ecosystem. This review highlighted the importance of the combined use of optical and microwave data and of the integration of the remote sensing products with the fi eld-based information for understanding the functioning of Amazonian ecosystems, its composition and the stressing factors (e.g., deforestation, fi re, droughts) that can directly impact this biome.